A NEW SPECIES OF ANADENDRUM (ARACEAE) FROM MALESIA - D. S. WlDYARTINI; ELIZABETH A WIDJAJA (REINWARDTIA, 1999)
A new species of Anadendrum ellipticum Widyartini & Widjaja, collected from Malay Peninsula, Kalimantan, North Sulawesi and Java proposed. This species is closely related with A. microstachyum but it differs on the structure of leaves, perianth and filament.